A single patch antenna with dual pairs of coupled modes for wide‐angle frequency beam scanning. Issue 8 (5th May 2022) - Liu, Gu; Zhang, Xuefeng; Shi, Jin
Abstract: A single patch antenna with dual pairs of coupled modes to achieve frequency beam scanning from backward to forward is proposed. The dual pairs of coupled modes are the odd‐ and even‐ TM10 and TM11 modes, which are caused by one row of metal vias near the middle of the patch. When the operating frequency is between the odd‐ and even‐ TM10 resonant frequencies, the beam scanning of the antenna is backward because of the positive phase difference between E x at the right and left edges. The forward beam scanning can be achieved between the odd‐ and even‐ TM11 resonant frequencies due to the negative phase difference between E y at the right and left parts. Therefore, the beam‐scanning angle can be expanded due to both backward and forward scanning. The measured results exhibit the 10‐dB impedance matching bandwidth of 6.3% (2.32–2.47 GHz) and 3.5% (3.34–3.46 GHz) for the lower and upper bands, in which the beam peak scans from −45° to 0° and from +9° to +36°, respectively.